2008
DOI: 10.1021/ja801662y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Polymers Prepared by ROMP with Unprecedented Selectivity: A Molecular Construction Kit Approach

Abstract: Synthetic Mimics of Antimicrobial Peptides (SMAMPs) imitate natural host-defense peptides, a vital component of the body’s immune system. This work presents a molecular construction kit that allows the easy and versatile synthesis of a broad variety of facially amphiphilic oxanorbornene-derived monomers. Their ring-opening metathesis polymerization (ROMP) and deprotection provide several series of SMAMPs. Using amphiphilicity, monomer feed ratio, and molecular weight as parameters, polymers with 533 times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
435
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(458 citation statements)
references
References 39 publications
18
435
2
2
Order By: Relevance
“…pDMAEMA was found to inhibit the growth of all the Gram-negative bacteria tested, with variable effects on the Gram-positive bacteria and no effect on the yeast. The selectivity for Gramnegative over Gram-positive bacteria has also been previously observed with other polymers 58,59 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…pDMAEMA was found to inhibit the growth of all the Gram-negative bacteria tested, with variable effects on the Gram-positive bacteria and no effect on the yeast. The selectivity for Gramnegative over Gram-positive bacteria has also been previously observed with other polymers 58,59 .…”
Section: Discussionsupporting
confidence: 77%
“…This value is similar to the MIC we found for the unconjugated polymer against E. coli ATCC 10536 (0.5 mg/ml). However, again, the bacteria were only exposed to the polymers for a short time ( Lienkamp et al 58 synthesized an array of polymers to mimic the effects of antimicrobial peptides. They found that some of their polymers were also more effective against Gramnegative than Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…in solution. In related work, a number of studies with polynorbornenes prepared via ROMP have shown promise for the development of multivalent ligands that can interact with cell surface proteins and be internalized by cells 120,121 , but here we only discuss work with polynorbornenes with polymeric side-chains and other related bottlebrushes.…”
Section: Non-associating Bottlebrushes For Encapsulation and Deliverymentioning
confidence: 99%
“…[65][66][67][68] By varying the specific structures of cationic groups and hydrophobic groups, the antimicrobial activity against particular microbes can be selectively enhanced as well. [69][70][71][72][73][74][75][76][77] It should be noted that the physical chemistry behind the globally amphiphilic antimicrobial cationic polymers needs to be studied furthermore for providing the guidelines for fabrication of antimicrobial materials with tailor-made structures and functions.…”
Section: Antimicrobial Polymers Y Yang Et Almentioning
confidence: 99%